Study of Trends in the Formation of Energy Intensity of Production and the Structure of "Energy Portfolio" - Malysheva, Tatyana V.; Ishmuradova, Izida I.; Yarlychenko, Alla A. (International Journal of Energy Economics and Policy, 2020)
The goal of the article is to define factors that influence formation of energy intensity and structure of "energy portfolio" in petrochemical manufacture and production. One of the basic research methods applied in the article is to use the method of correlation analysis for connection detection between specific energy resource consumption, dynamic factor analysis for types of comments determination into factor formation of energy intensity in production, method of main part and criteria of "stony cree" for identification of dominant factors and tendency in energy intensity formation. The article has the analysis of dynamics and structure of specific consumption of energy resources on production of each type of petrochemical types of production. There is an interconnection between increase rate of specific electric and thermal consumption. Key factors and tendency formation of energy intensity and structures of "energy portfolio" by types petrochemical manufacture were identified. Research materials may be used to develop public documents of strategic planning, pioneering projects for introduction of resource saving technologies, monitoring performance of efficiency implementation in energy-saving programs. Identified tendencies and consistent patterns will introduce purposeful impact on certain performance types with the aim of energy intensity cause increase identification in production and decision development to organize energy-saving manufacture. Keywords: energy efficiency, product energy intensity, energy resources, thermal energy, energy portfolio, energy saving technologies. JEL Classifications: Ðž14, D24, Ð¡38 DOI: https://doi.org/10.32479/ijeep.9545